Muslim consumers' awareness and perception of halal food fraud - Ruslan, Akma Aizatul Ain; Kamarulzaman, Nitty Hirawaty; Sanny, Maimunah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Halal food represents up to 20% of the entire global halal food industry is one of the most profitable and influential market areas with the increasing of world Muslim population. Halal is an important aspect in the selection of food as it is one’s part to obey with religious obligations and commandments. Since halal food industry covers ‘farm to table’ operations, the issue of food fraud along the food supply chain become a major concern. Food fraud, in general, is defined as a substitute, adding, misrepresenting of food label or a food ingredient or misleading statement about the products intentionally for economic gain. Thus, this study was carried out with the objectives of this study are 1) to determine Muslim consumers’ awareness and perception of Halal food fraud, 2) to identify the association between socio-demographic profiles and consumers’ awareness of Halal food fraud products and 3) to investigate factors that influence consumers’ perception of Halal food fraud. The conceptual framework used for this study was adapted from Ambali and Bakar (2014). A total of 352 respondents participated in this study was selected using a simple random sampling in Klang Valley. Data were analysed using descriptive analysis, Chi-square analysis, and factor analysis. The results indicated that majority of the respondents in Klang Valley were aware of Halal food fraud. However, there were some respondents who have previous experience on buying Halal food fraud products. Gender, age, education level and occupation were important factors that have significant relationships with Halal food fraud issues. Factor analysis identified three factors that influence the consumers’ perception towards Halal food fraud which included consumer attitude, authorities exposure and control and Halal logo, labelling and packaging. This study also found that Halal food fraud was sold in the Malaysia market but Muslim consumers were found to have difficulty to still differentiate between original products and fraud products.